2011
DOI: 10.1094/mpmi-06-11-0177
|View full text |Cite
|
Sign up to set email alerts
|

Barley Leaf Transcriptome and Metabolite Analysis Reveals New Aspects of Compatibility and Piriformospora indica–Mediated Systemic Induced Resistance to Powdery Mildew

Abstract: Colonization of barley roots with the basidiomycete fungus Piriformospora indica (Sebacinales) induces systemic resistance against the biotrophic leaf pathogen Blumeria graminis f. sp. hordei (B. graminis). To identify genes involved in this mycorrhiza-induced systemic resistance, we compared the leaf transcriptome of P. indica-colonized and noncolonized barley plants 12, 24, and 96 h after challenge with a virulent race of B. graminis. The leaf pathogen induced specific gene sets (e.g., LRR receptor kinases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 63 publications
8
77
1
2
Order By: Relevance
“…Moreover, systemic leaves of plants pretreated with the root-colonizing and plant growth-promoting fungus Piriformospora indica display enhanced resistance to Bgh (Waller et al, 2005). Similar to our leaf-to-leaf response, this root-to-leaf ISR response does not appear to be correlated with SA or JA signaling but with relatively few gene expression changes in the aboveground, systemic tissue (Waller et al, 2005(Waller et al, , 2008) that might prime the leaves for both apoplast alkalinization and expression changes of a specific set of genes, including three PR genes, upon Bgh infection (Felle et al, 2009;Molitor et al, 2011). Alternatively, leaf-to-leaf and root-to-leaf systemic immune responses might be primed independently of the (limited) gene expression changes observed in the putatively primed tissue but instead might be regulated by, for example, posttranslational protein modifications (Beckers et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, systemic leaves of plants pretreated with the root-colonizing and plant growth-promoting fungus Piriformospora indica display enhanced resistance to Bgh (Waller et al, 2005). Similar to our leaf-to-leaf response, this root-to-leaf ISR response does not appear to be correlated with SA or JA signaling but with relatively few gene expression changes in the aboveground, systemic tissue (Waller et al, 2005(Waller et al, , 2008) that might prime the leaves for both apoplast alkalinization and expression changes of a specific set of genes, including three PR genes, upon Bgh infection (Felle et al, 2009;Molitor et al, 2011). Alternatively, leaf-to-leaf and root-to-leaf systemic immune responses might be primed independently of the (limited) gene expression changes observed in the putatively primed tissue but instead might be regulated by, for example, posttranslational protein modifications (Beckers et al, 2009).…”
Section: Discussionsupporting
confidence: 73%
“…Cordova-Campos et al (2012) found that basal resistance to Pseudomonas syringae pathovars was signifi cantly greater in wild accessions of bean Phaseolus vulgaris than in modern cultivars. In a recent work on barley, Molitor et al (2011) demonstrated that following inoculation of powdery mildew infected plant with Piriformospora indica, there was a priming of powdery mildew defuse-associated genes at an early stage of the infection.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the main effects of this fungus were not remarkable, resulting in no significant induction in transcription of the studied antioxidant genes. Therefore, influence of mix-colonization treatment, particularly in Molitor et al (2011) indicated that P. indica could induce transcription of a wide range of pathogenesis-related genes and they concluded that P. indica likely induced disease resistance through genes encoding heat-shock proteins.…”
Section: Effects Of Fungal Treatments On H 2 O 2 Content and Enzyme Amentioning
confidence: 99%